ITGB4 deficiency in airway epithelia enhances HDM-induced airway inflammation through hyperactivation of TLR4 signaling pathway. Issue 2 (16th January 2023) - Zhou, Kai; Yuan, Lin; Liu, Huijun; Du, Xizi; Yao, Ye; Qin, Ling; Yang, Ming; Xu, Kun; Wu, Xinyu; Wang, Leyuan; Xiang, Yang; Qu, Xiangping; et al.
Abstract: Airway epithelial cells (AECs) are the first cell barrier of the respiratory system against external stimuli that play a critical role in the development of asthma. It is known that AECs play a key role in asthma susceptibility and severity. ITGB4 is a downregulated adhesion molecule in the airway epithelia of asthma patients, which was involved in the exaggerated lung inflammation after allergy stimulation. Toll-like receptor 4 (TLR4) in AECs has also been shown to play a crucial role in the development of lung inflammation in asthma patients. However, the specific intrinsic regulatory mechanism of TLR4 in AECs are still obscure. In this article, we demonstrated that ITGB4 deficiency in AECs enhances HDM-induced airway inflammation through hyperactivation of the TLR4 signaling pathway, which is mediated by inhibition of FYN phosphorylation. Moreover, TLR4-antagonist treatment or blockade of FYN can inhibit or exaggerate lung inflammation in HDM-stressed ITGB4-deficient mice, separately. Together, these results demonstrated that ITGB4 deficiency in AECs enhances HDM-induced lung inflammatory response through the ITGB4-FYN-TLR4 axis, which may provide new therapeutic approaches for the management of lung inflammation in asthma. Abstract : Deficiency of ITGB4 in airway epithelial cells induces enhanced Th2-type inflammatory response after HDM stress by inhibiting FYN phosphorylation and upregulating the TLR4 signaling pathway.